2004
DOI: 10.1159/000078616
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hormone Replacement Therapy on Ocular Surface and Tear Function Tests in Postmenopausal Women

Abstract: Purpose: To prospectively investigate the impact of various hormone replacement therapies (HRT) on ocular surface and tear function tests. Methods: A total of 70 women in the postmenopausal period were enrolled in the study. The groups consisted of 16 women who were not on HRT (group 1), 29 women who were on HRT with tibolone (group 2) and 25 women who received estradiol plus medroxyprogesterone acetate treatment (group 3). All patients underwent tear film break-up time (TFBUT), Schirmer’s test and conjunctiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Tear production decreases after menopause (Altintas et al 2004). Although some studies have found that hormone replacement therapy (HRT) leads to a decrease in tear function (Schaumberg et al 2001, Uncu et al 2006, the majority have shown that dry eye improves after HRT (Affinito et al 2003, Guaschino et al 2003, Altintas et al 2004, Taner et al 2004, Coksuer et al 2011). In addition, topical E 2 drops appear to alleviate dry eye symptoms Synthesis of oestrogens.…”
Section: The Eyementioning
confidence: 99%
“…Tear production decreases after menopause (Altintas et al 2004). Although some studies have found that hormone replacement therapy (HRT) leads to a decrease in tear function (Schaumberg et al 2001, Uncu et al 2006, the majority have shown that dry eye improves after HRT (Affinito et al 2003, Guaschino et al 2003, Altintas et al 2004, Taner et al 2004, Coksuer et al 2011). In addition, topical E 2 drops appear to alleviate dry eye symptoms Synthesis of oestrogens.…”
Section: The Eyementioning
confidence: 99%
“…Some studies showed an increase in goblet cell density responsible for the production of mucous layer of the tears [4] where other studies did not find the same results [6], and this warrants further clarification. After using HRT for 3 months in 17 postmenopausal women, Pelit et al [4] found significant changes in conjunctival epithelium with an increase in goblet cell density, and also in those women, the dry eye syndrome symptoms was relieved.…”
Section: Conjunctivamentioning
confidence: 95%
“…After using HRT for 3 months in 17 postmenopausal women, Pelit et al [4] found significant changes in conjunctival epithelium with an increase in goblet cell density, and also in those women, the dry eye syndrome symptoms was relieved. After 6 months use of tibolone, the cytology of the conjunctiva is not different as compared with women who received estrogen and progesterone and those who had no HRT treatment [6]. Kuscu et al [5], using 6 months estrogen and progesterone in postmenopausal, showed no significant change in the conjunctival vascular congestion or the degree of its laxity.…”
Section: Conjunctivamentioning
confidence: 96%
See 1 more Smart Citation
“…18,19 Other agents such as secretogogues, other immune mediators, and androgens are currently being evaluated. [20][21][22][23][24][25][26] Topical cyclosporine blocks T-cell activation, reducing the production of inflammatory cytokines that recruit additional T cells and incite inflammatory T-cell inhibition of lacrimal tear production. 27,28 This leads to an increase in the quality and quantity of tears and decreases the damage to lacrimal gland tissue and the ocular surface.…”
mentioning
confidence: 99%